Different approaches to the treatment of skeletal Class II malocclusion during growth: Bionator versus extraoral appliance - Renato Barcellos Rédua
ABSTRACT Introduction: Class II malocclusion, which has a significant incidence in the population, may compromise facial esthetics and the smile, as well as the masticatory and respiratory functions. Often associated with skeletal abnormalities, it severely affects and compromises quality of life. An accurate diagnosis is fundamental to prepare a treatment plan to correct dental and skeletal anomalies. Objectives: This study discusses treatment alternatives to the correction of Class II division 1 and 2 malocclusion in growing patients, using a Bionator and an extraoral appliance.